Is Severe Pain Immediately after Spinal Augmentation a Predictor of Long-Term Outcomes? - Cho, Y.W. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Severe, immediate postprocedural pain and the need for analgesics after vertebroplasty can be a discouraging experience for patients and caregivers. The goal of this study was to investigate whether the presence of severe pain immediately after vertebroplasty predicts short- and long-term pain relief. MATERIALS AND METHODS: A chart review was performed to categorize patients regarding pain severity and analgesic usage immediately after vertebroplasty (< 4 h). “Severe” pain was defined as at least 8 of 10 with the 10-point VAS. Outcomes were pain severity and pain medication score and usage at 1 month and 1 year after vertebroplasty. Outcomes and clinical characteristics were compared between groups by using the Wilcoxon signed-rank test and the Fisher exact test. RESULTS: Of the 429 vertebroplasty procedures identified, 69 (16%) were associated with severe pain, and 133 (31%) were associated with analgesic administration immediately after the procedure. The group experiencing severe pain had higher preprocedure median VAS rest pain scores (5 [IQR, 2–7]) and activity pain scores (10 [IQR, 8–10]) compared with patients who did not experience severe pain (3 [IQR, 1–6]; P = .0208, and 8 [IQR, 7–10]; P = .0263, respectively). At 1 month postprocedure, VAS rest and activity pain scores were similar between the severe pain group and the nonsevere pain group (P = .16 and P = .25, respectively) and between the group receiving pain medication and the group not receiving pain medication (P = .25 and P = .67, respectively). This similarity continued for 1 year after the procedure. Analgesic usage was similar among all groups at 1 year postprocedure. CONCLUSIONS: Patients with severe pain immediately after vertebroplasty have similar long-term outcomes compared with patients without severe pain.